Sierra Leone : Request for An Extended Arrangement Under the Extended Credit Facility-Press Release; Debt Sustainability Analysis; Staff Statement; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report ;, 2018)
Sierra Leone is a fragile state. Since emerging from a decade-long civil war in 2001, the country has made notable economic progress but has also suffered occasional setbacks, such as the Ebola Virus Disease epidemic of 2014. A three-year ECF arrangement was approved June 2017 to help address Sierra Leone's macroeconomic weaknesses-in particular, low revenue, elevated inflation, high public debt, and inadequate foreign exchange reserve buffers-which had been exacerbated by the Ebola crisis and a collapse in iron ore prices (Country Report No. 17/154). However, the program went off track shortly after approval as lackluster revenue performance and expenditure overruns led to a budget cash shortfall and a growing stock of budget arrears. With the authorities unable to take corrective actions ahead of the March 2018 presidential elections the first review of the program was put on hold. Since then elections have produced a new government, marking the first change of power in ten years. This government has taken a number of corrective actions over the last six months with the aim of reviving the program engagement with the IMF.